Metode Penyimpanan Semai Bakau (Rhizopora apiculata) dengan berbagai kondisi tempat dan Media simpan serat bahan penghambat pertumbuhan - Dida Syamsuwida; Aam Aminah (Jurnal Pemuliaan Tanaman Hutan, 2010)
Bakau (Rhizopora apiculata(, one of the species of mangrove, is well known for having true recalcitrat seeds, since they tend to have very short-life cycle. Hence they cannot be stored a long time. Developing improved methods for retarding seedling growth of tropical mangrove is necessary to successfully control growth rates during long-term storage. The aim of the research is to identify the influence of growth inhibitors used were paclobutrazol (250 ppm), NaCl (0,5 %) and aquadest (as a control). The condition for the storage consists of heavy (650 lux), moderate (8935 lux) and light (17593 lux) shadings. The media used including the mixture of sand. A completely randomized design was arranged in a factorial experiment. The results showed that the use of paclobutrazol (250 ppm) was very effective to suppress the growth height of the seedlings. The storage condition of light shading with the intensity of the  day-light and the highest temperatur (L.I= ±17593 lux, T= ±350C) could reduced the speed of seedling growth during storage for 6 months supported by the use of sand as media. Such conditions gave a seedling survival of 98,33%